IS management handbook - Brown, Carol V. (Carol Vanderbilt) 1945-; Topi, Heikki (Auerbach Publications, 2003)
Focuses on maximizing the performance of resources during tough economic times. This book provides information that allows IT managers to effectively organize people and processes, and efficiently integrate and maintain infrastructure, applications, support systems, e-business tools, and databases.